PERANCANGAN DESAIN UI/UX SISTEM INFORMASI MANAJEMEN UMKM WARUNG OMBAY MALA - Sari, Riska Maya; Supratman, Edi (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2026)
The rapid advancement of information technology in the digital era provides significant opportunities for Small and Medium Enterprises (SMEs) to enhance efficiency and competitiveness through the utilization of digital-based systems. However, Warung Ombay Mala, a culinary SME selling chicken meatball soup, tekwan, and model, still manages its transactions and sales records manually. This situation often leads to challenges in data management, inventory control, and the preparation of financial reports. Therefore, a management information system is needed to support operational processes in a more structured and accurate manner. An essential stage in the system development process is the design of the user interface and user experience (UI/UX), which ensures that the system is easy to use for both the owner and employees. This study aims to design the UI/UX for the Management Information System of Warung Ombay Mala by conducting user needs analysis, developing wireframes, creating prototypes, and testing the design using usability testing principles. The design focuses on producing an interface that is simple, interactive, and functional while also supporting the process of determining the cost of production using the Full Costing method. The results of the study show that the digitally based ordering system design significantly simplifies transaction processes for both customers and the business owner. The resulting UI/UX design meets user needs through its intuitive, consistent, and responsive layout. Features such as menu ordering, topping customization, digital payment options, and order receipt printing successfully enhance the efficiency of the ordering workflow. Overall, this design has strong potential to improve service quality, reduce recording errors, and promote sustainable digitalization for SMEs.Keywords: UI/UX, Information System, SME, Warung Ombay Mala, Digitalization